USING ALTERNATIVE ASSESSMENT TECHNOLOGIES TO PROMOTE ACTIVE LEARNING - MANUKYAN, ANI (IJRDO- Journal of Educational Research, 2017)
The author tries to define alternative assessment as an act of acquiring and analyzing informationabout students for a purpose, identifying and diagnosing the special educational needs ofeducation and informing planning for further actions. It forms an integral part of the process ofproviding support and educational wherewithal. This information includes knowledge about anindividual’s personality, way of thinking and style of learning, as well as it helps to discoverhis/her cognitive abilities, environmental status, academic achievement and social competence.In this paper we consider each type of assessment, highlight the relative strengths andweaknesses of each one, and discuss how teachers can choose among many options with twoprimary considerations: the importance of the effect and the crucial need to use multiple sourcesof information.The article also dwells on the effective ways of developing alternative assessment to promoteactive learning. Our next step is the sharing of the results of the survey methods we considerparticularly productive in assessing alternatively. To reach our aims we organized a range ofexperimental lessons, conducted surveys with questionnaires and organized a debate to provethat set of activities chosen by us can enrich and reinforce the students’ comprehension ofalternative assessment, as well as it can stimulate the usage of alternative assessment in thepractice of teachers